Cyber‐physical systems opportunities in the chemical industry: A security and emergency management example. Issue 4 (7th April 2014) - Squire, Richard; Song, Houbing
<x xml:space="preserve">Abstract</x> The manuscript defines and discusses the products of a successful cyber‐physical system in the chemical industry using two examples. The first is the ability to make the correct decision quickly regarding an unforecasted large sale of a product. The second is the automatic availability of critically needed information, accessible anywhere in the world which provides endless possibilities for the chemical industry. Concerns and some resolutions are also discussed. © 2014 American Institute of Chemical Engineers Process Saf Prog 33: 329–332, 2014